Communication in symbiotic associations: mechanisms between arbuscular mycorrhizal fungi, plants and soil organisms - Watson-Guido, William; Rivera-Méndez, William (Agronomía Mesoamericana, 2024)
Introduction. Arbuscular mycorrhizal fungi (AMF) form close symbiotic associations with 90 % of plant species. They engage in a molecular dialogue using infochemicals and nutrient molecules to regulate this mutualistic association. Objective. To gather information on the molecular mechanisms involved in the communication between AMF, their host plant and other soil organisms. Development. The symbiosis between mycorrhizal fungi and plants depends on specific signaling molecules that allow recognition, signaling and communication, in addition to physical contact between both organisms. The mechanisms of molecular communication and biological interactions between AMF and plants at different times of interaction are described, with emphasis on the description of currently known regulatory genes, proteins and target molecules. Additionally, molecular interactions with other soil organisms are described. Conclusions. The mechanisms of molecular communication between mycorrhizal fungi and plants are complex and still present gaps in knowledge that must be filled to fully understand the ecological importance of AMF and their interactions with other edaphic organisms, and thus achieve their use.